Zuñi coyote tales - Cushing, Frank Hamilton, 1857-1900 (Book collections on Project MUSE., 1998)
Coyote Tales are among the best loved in Native American folklore, and those collected by anthropologist Frank Hamilton Cushing at the end of the nineteenth century have well survived the test of time. This collection of authentic stories, extracted from the classic Zuni Folk Tales, offers modern readers of all ages a new appreciation of magic and myth as celebrated by the Zuni Indians of western New Mexico.